INFORMATION ANALYSIS AND SYSTEMATISATION OF THE STATE OF THE ART IN RESEARCH AND DEVELOPMENT OF TECHNOLOGIES FOR COMPUTER CONTROL OF GRAIN CROPS MOISTENING MODES - DIACHENKO, GRYGORII; KREMNOV, VOLODYMYR; KOVAL, VALERII; YEVSTRATIEV, MYKHAILO (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The global intensification of the use of land resources for agricultural purposes and the simultaneous negative dynamics of cultivated areas in Ukraine necessitate the substantiation of effective approaches and technologies for controlling critical parameters and the general condition of land resources when cultivating crops in open-field conditions. Soil moisture is one of the crucial factors in the justification and implementation of measures to increase soil productivity and improve crop stress resistance. Effective control of soil moisture prevents soil erosion and improves the regularity of river flow, which has a significant environmental and economic effect in the course of open-field crop production. The aim of the research is to substantiate the requirements for the creation of computer technologies for the predictive control of soil moistening modes in order to improve the efficiency of agrotechnical measures for the cultivation of grain crops through a comprehensive information analysis and systematisation of modern applied information and computer technologies. The object of the research is information processes of detection, network exchange and predictive processing of a set of distributed data on the modes of moistening of grain crops. The subject of the research is models, methods and hardware and software means of creating computer technologies for the predictive control of grain crop moistening modes. General trends in agricultural activities for growing grain crops at the national and global level have been analysed; functional and technological features, as well as models, methods and means of computerised intelligent control of soil moistening modes in the process of growing grain crops, have been analysed in detail; world experience in the creation and utilisation of software and hardware for the computerised intelligent control systems of soil moisture has been analysed and systematised; the necessity of further research on the development of effective approaches to optimising the modes of growing of grain crops through the creation and implementation of computer technologies for the predictive control of the state of agricultural objects of the open-field crop production has been proved.